Effect of Natural Marination Based on Apple Vinegar and Acid Whey on Volatile and Sensory Profile, Safety, and Physicochemical Properties of Raw Fermented Beef Hams - Barbara Sionek; Anna Okoń; Anna Łepecka; Agata Antoniewska-Krzeska; Piotr Szymański; Danuta Jaworska; Jarosława Rutkowska; Danuta Kołożyn-Krajewska (Agriculture)
Consumers appreciate fermented meat products due to their nutritional value and unique taste. Fermented fruit vinegar used traditionally to preserve food is characterized by a high content of nutrients and bioactive ingredients. Acid whey has antioxidant and antibacterial properties and can provide probiotic lactic acid bacteria (LAB). Three variants of the fermented beef hams were produced: AW—1.5% salt and 5% acid whey, A—1.5% salt and 5% apple vinegar, and C—1.5% salt. The effect of natural marination, based on apple vinegar and acid whey on volatiles, physicochemical and microbiological parameters, and sensory quality of the raw fermented beef hams was assessed. The highest pH and the lowest oxidation–reduction potential value (ORP) was found for A hams after production and after storage (p < 0.05). AW hams had the highest Thiobarbituric Acid-Reactive Substances (TBARS) value after production (6.07 mg MDA/kg) and after 8 months of storage (6.12 mg MDA/kg) (p < 0.05). The AW and A hams showed moderate overall sensory quality after production and after storage (above 5 c.u.). Both treatments modify the formation and stability of volatile compounds, not affecting the overall quality. The number of LAB in raw fermented beef hams with acid whey and apple vinegar was high (approximately 7 log CFU/g) after 3 months, and this decreased after 8 months of storage to 6.24 and 5.83 log CFU/g, respectively, for AW and A treatment. Among sixty volatile compounds, an abundance of aldehydes, carboxylic acids, esters, and alcohols dominated, which contributed to the formation of aroma attributes of beef hams. This study demonstrates that apple vinegar and acid whey can be used for the production of microbiologically safe fermented beef hams with good sensory quality.